Ventilation and perfusion magnetic resonance imaging of the lung - Bauman, Grzegorz (International Scientific Literature, Inc., 2012)
A close interaction between the respiratory pump, pulmonary parenchyma and blood circulation is essential for a normal lung function. Many pulmonary diseases present, especially in their initial phase, a variable regional impairment of ventilation and perfusion. In the last decades various techniques have been established to measure the lung function. Besides the global pulmonary function tests (PFTs) imaging techniques gained increasing importance to detect local variations in lung function, especially for ventilation and perfusion assessment. Imaging modalities allow for a deeper regional insight into pathophysiological processes and enable improved planning of invasive procedures. In contrast to computed tomography (CT) and the nuclear medicine techniques, magnetic resonance imaging (MRI), as a radiation free imaging modality gained increasing importance since the early 1990 for the assessment of pulmonary function. The major inherent problems of lung tissue, namely the low proton density and the pulmonary and cardiac motion, were overcome in the last years by a constant progress in MR technology. Some MR techniques are still under development, a process which is driven by scientific questions regarding the physiology and pathophysiology of pulmonary diseases, as well as by the need for fast and robust clinically applicable imaging techniques as safe therapy monitoring tools. MRI can be considered a promising ionizing-free alternative to techniques like CT or nuclear medicine techniques for the evaluation of lung function. The goal of this article is to provide an overview on selected MRI techniques for the assessment of pulmonary ventilation and perfusion.